'Intimately associated for many years' . George A.K. Bell's and Willem A. Visser't Hooft's common life-work in the service of the church universal, mirrored in their correspondence /: George A.K. Bell's and Willem A. Visser't Hooft's common life-work in the service of the church universal, mirrored in their correspondence. 1950-1958 : Part two, (2015) - Bell, G. K. A (George Kennedy Allen), 1883-1958; Visser 't Hooft, Willem Adolph, 1900-1985
No abstract available